2013 IEEE International Conference on Healthcare Informatics 2013
DOI: 10.1109/ichi.2013.89
|View full text |Cite
|
Sign up to set email alerts
|

Why Majority of Readmission Risk Assessment Tools Fail in Practice

Abstract: Focus on readmission risk assessment tools has never been higher, and yet for all the time, resources, and attention spent developing and implementing these disparate models, readmission rates have barely budged. Fundamental flaws exist in most approaches in the areas of Data, Model Adaptability, and Clinical Workflow Integration. Many tools rely solely on historical patient data mined from the EHR or on disease-specific models that cannot be scaled to address all readmissions challenges. Models that rely on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In two systematic reviews [ 8 , 12 ] of 99 readmission predictive models reported between 1985 and 2015, 77% of the models were specialized for one patient subpopulation. The condition-specific design limits the adaptability of the models to other patient subpopulations and may overlook patients in some at-risk minority groups if specific models are not available [ 49 , 50 ]. In practice, it can be challenging for a hospital to maintain separate readmission prediction models for different patient subpopulations, and this situation will be further exacerbated if patients have comorbidities [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two systematic reviews [ 8 , 12 ] of 99 readmission predictive models reported between 1985 and 2015, 77% of the models were specialized for one patient subpopulation. The condition-specific design limits the adaptability of the models to other patient subpopulations and may overlook patients in some at-risk minority groups if specific models are not available [ 49 , 50 ]. In practice, it can be challenging for a hospital to maintain separate readmission prediction models for different patient subpopulations, and this situation will be further exacerbated if patients have comorbidities [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The condition-specific design limits the adaptability of the models to other patient subpopulations and may overlook patients in some at-risk minority groups if specific models are not available [ 49 , 50 ]. In practice, it can be challenging for a hospital to maintain separate readmission prediction models for different patient subpopulations, and this situation will be further exacerbated if patients have comorbidities [ 50 ]. All-cause models are designed for broad patient populations without limiting diagnoses or procedures.…”
Section: Discussionmentioning
confidence: 99%
“…However, their current performance is not su cient for a wider use. Furthermore, explaining the reasons for a potential 30-day readmission understood by the physician is still a challenge for the ease of medical decision making in the current clinical practice [25].…”
Section: Discussionmentioning
confidence: 99%
“…The choice between conditionspecific and all-cause readmission models has long been under debate. However, condition-specific models have been criticized for the poor generalizability, especially in patients with multiple conditions [8,9]. In addition, readmissions are not always clinically relevant to the index admissions.…”
Section: Introductionmentioning
confidence: 99%